Moving from hand to mouth: echo phonology and the origins of language - Woll, Bencie (Frontiers in Psychology, 2014)
Although the sign languages in use today are full human languages, certain of the features they share with gestures have been suggested to provide information about possible origins of human language. These features include sharing common articulators with gestures, and exhibiting substantial iconicity in comparison to spoken languages. If human proto-language was gestural, the question remains of how a highly iconic manual communication system might have been transformed into a primarily vocal communication system in which the links between symbol and referent are for the most part arbitrary. The hypothesis presented here focuses on a class of signs which exhibit: 'echo phonology', a repertoire of mouth actions which are characterized by 'echoing' on the mouth certain of the articulatory actions of the hands. The basic features of echo phonology are introduced, and discussed in relation to various types of data. Echophonology provides naturalistic examples of a possible mechanism accounting for part of the evolution of language, with evidence both of the transfer of manual actions to oral ones and the conversion of units of an iconic manual communication system into a largely arbitrary vocal communication system.